Analysis of the Narrative Structure of Isrāiliyyāt: A Study on the Isrāiliyyāt Accounts of Dawud in Al-Tha’labi’s Exegesis Al-Kashf wa al-Bayān ‘an Tafsīr al-Qur’ān - Moh. Muhyiddin; Luthfillah, Muhammad Dluha (QOF, 2023)
Isrāiliyyāt entered and developed in the interpretations as al-dakhīl can't be avoided. However isrāiliyyāt is a matter of debate and received a lot of criticism. This paper examined how the narrative structure isrāiliyyāt about the story of Prophet Dawud in Tafsir Al-Kashf wa al-Bayān ‘an Tafsīr al-Qur’ān written by Al-Tha'labi. Isrāiliyyāt about the story of the prophet Dawud is analyzed with a narrative structure, in which is one of the most crucial types of discourse. The purpose of this research was to know the narrative structure in the narrative isrāiliyyāt which is obtained from narration in tafsir Al-Kashf wa al-Bayān 'an Tafsīr al-Qur'ān. This study used a qualitative method with narrative analysis as a basis for discussing narrative structure. Narrative analysis was used to seek the narrative isrāiliyyāt the story of the prophet Dawud who is expected to know how al-Tha'labi expresses the story in such a way that the reader can grasp the story of the prophet Dawud. Here, After analyzing the text, the author finally concluded the inner narrative structure isrāilliyat, the results are (a) orientation, (b) complication, (c) evaluation, (d) resolution, and (e) coda. The narrative contribution also results in the story of the Prophet Dawud chronologically, namely the Prophet Dawud before receiving trials, the Prophet Dawud receiving trials and the Prophet Dawud after repenting.